Sexual Dimorphism of Adipose and Hepatic Aquaglyceroporins in Health and Metabolic Disorders - Rodríguez, Amaia; Marinelli, Raul A.; Tesse, Angela; Frühbeck, Gema; Calamita, Giuseppe (Frontiers in Endocrinology, 2015)
Gender differences in the relative risk of developing metabolic complications, such as insulin resistance or non-alcoholic fatty liver disease (NAFLD), have been reported. The deregulation of glycerol metabolism partly contributes to the onset of these metabolic diseases, since glycerol constitutes a key substrate for the synthesis of triacylglycerols as well as for hepatic gluconeogenesis. The present minireview covers the sex-related differences in glycerol metabolism and aquaglyceroporins (AQPs) and its impact in the control of adipose and hepatic fat accumulation as well as in whole-body glucose homeostasis. Plasma glycerol concentrations are increased in women compared to men probably due to the higher lipolytic rate and larger AQP7 amounts in visceral fat as well as the well-known sexual dimorphism in fat mass with women showing higher adiposity. AQP9 represents the primary route for glycerol uptake in hepatocytes, where glycerol is converted by the glycerol kinase enzyme into glycerol-3-phosphate, a key substrate for de novo synthesis of glucose and triacylglycerol. In spite of showing similar hepatic AQP9 protein, women exhibit lower hepatocyte glycerol permeability than men, which might contribute to their lower prevalence of insulin resistance and NAFLD.